Does credit constraint in agriculture influence choice of nonfarm activities? evidence from rural Nigeria (2019)
Agriculture is less becoming the main source of livelihood in rural Nigeria owing to high climatic risks, poor returns to investment and lack of modern tools. Thus, rural households are beginning to diversify their livelihoods from farming into non-farm activities, as alternative income sources. However, investment in non-farm income generating activities that yield higher returns require in most cases credit availability and accessibility. A household’s participation in and choice of nonfarm activities is thus expected to vary significantly between those who have access to credit and those who do not. However, recognition of the widespread nature and possibly far-reaching impacts of credit on non-farm income activities is scarce. This study examines the link between credit constraint status of rural households and their choice of nonfarm activities. Descriptive statistics, Probit and Multinomial Logit Regression models were employed for analysis. Results revealed that trading, artisanship and commercial transportation activities were the major non-farm activities engaged in by the households. A household credit constrained status also significantly influenced the choice of non-farm activities. Credit constrained households were more likely to participate in commercial transportation activities relative to other non-farm activities owing to its less capital-intensive nature. Promoting access to credit is thus pertinent and should be of utmost priority in the design of any programme for rural households in Nigeria.